Beyond Tangible Resources: Strategic Capabilities in Platform-Based Business Models - Akbar, Taufik; Syifa Awalia,, A. Agung Feinnudin, Muhamad Erwin Kurniawan,; Agung Wahyu Handaru, Indra Pahala, (YUME : Journal of Management, 2025)
The transition from traditional asset-heavy business models to platform-based businesses highlights the increasing importance of intangible resources in sustaining competitive advantage. This study critically examines the limitations of the classic Resource-Based View (RBV), which traditionally emphasizes owned assets, and explores its adaptation to digital platform firms that leverage data, network effects, and strategic orchestration. Using a systematic literature review approach, the study identifies five core capabilities—ecosystem coordination, scalable digital systems, data-driven decision-making, user trust-building, and fast innovation cycles—as fundamental to platform success. Findings suggest that competitive advantage in the digital economy stems from managing rather than owning resources. This research contributes to the strategic management discourse by extending the RBV to incorporate orchestration and relational assets as critical determinants of success in platform-based business models.Keywords: Resource-Based View (RBV); platform-based business models; digital capabilities; strategic orchestration; network effect.